The Relationship between the Quality of Physiotherapy Services and the Level of Satisfaction of Patients with Musculoskeletal Cases Physiotherapy Independent Practice in Malang Raya - Trizah Ardha Widyaningtyas Sutiyo; Safun Rahmanto; Dimas Sondang Irawan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Objective: To determine the relationship between the quality of physiotherapy services and the level of patient satisfaction with musculoskeletal cases of independent practice of physiotherapy in Malang Raya. Methods: Observational analytic research design approach cross sectional design. The sample in this study is The sample of this study were patients with musculoskeletal cases who underwent independent practice physiotherapy in Malang Raya and were willing to be part of the sample. Sample technique using convenience sampling with a total sample of 35 people. Data collection tool for service quality using Instruments Servqual and patient satisfaction using the Medrisk Instrument. Test Data analysis was carried out then normality test, correlation test using test pearson rhu in the SPSS program. Results: Based on the results of the significance value correlation test (2-tailed) 0.000 indicates a value <0.05 with information H0 is rejected and H1 is accepted. Pearson Correlation of 0.642**, which is included in the category of strong relationship level. Conclusion: that there is a correlation between the quality of service and the level of patient satisfaction with musculoskeletal cases of independent practice of physiotherapy in Malang Raya.